PEMANFAATAN DAUN JUWET SEBAGAI ANTIOKSIDAN (SYZYGIUM CUMINI L.) PADA MASYARAKAT RT 09, KELURAHAN LAMBARA, KECAMATAN TAWEILI SULAWESI TENGAH - tuldjanah, Muthmainah; Budiawan, Erick; Paga, Fajria Rezky Priyanti Amara; Vegyn, Vegyn; Mu’min, Nur Hijrah (Jurnal Abdi Insani, 2025)
Juwet leaves (Syzygium cumini L.) are plants with antioxidant content that can protect the body from free radicals that cause degenerative diseases. The community of RT 09, Lambara Village has access to juwet plants that grow naturally in the surrounding environment, but their level of knowledge and understanding of the benefits of juwet leaves as a source of natural antioxidants is still low. This community service activity aims to increase the knowledge and understanding of the community of RT 09, Lambara Village, Taweili District regarding the benefits of juwet leaves as a source of natural antioxidants for health. Education was carried out through a lecture method with posters and brochures, followed by a question and answer session. Evaluation of the program's success was carried out by providing a pre-test before education and a post-test after education to 45 participants from the RT 09 community using a 4-question instrument related to knowledge about juwet leaves and antioxidants. The community service activity carried out on November 30, 2024, was attended by 45 participants and ran smoothly. The evaluation results showed a very significant increase in community knowledge. In the pre-test, the community's understanding level ranged from 32-44% for the four aspects measured (knowledge of the benefits of juwet leaves, the definition of antioxidants, the importance of antioxidants, and dosage). After providing educational materials, post-test results showed an increase in understanding to 90-98%. The participants' enthusiasm was evident in their active participation in the question and answer session and their positive appreciation for the program. The educational program on the use of juwet leaves as an antioxidant succeeded in significantly increasing the knowledge of the community in RT 09, Lambara Village, as indicated by an increase in the understanding score from 32-44% (pre-test) to 90-98% (post-test).